INOVASI, PERTUMBUHAN, UKURAN DAN NILAI PERUSAHAAN FARMASI DI INDONESIA - Mursalim Nohong (University of Merdeka Malang, 2016)
Abstract This research was based on the strategic role of firm innovation. For a pharmaceutical company, innovation drives the firm to expand new product which responsive to the needs of public health. The purpose of this study was to explain the innovation role on growth, size, and the value of pharmaceuticalcompany in Indonesia. Secondary data with a period of 2011 - 2014 of ten sample used were pharmaceutical companies listed on the Indonesia Stock Exchange.Data were analyzed using Structural Equation Modeling with PLS. The research results show that innovation were able to increase growth, size and companyvalue.